LAS616: Cultural Landscape Study / College of Built Environment - UiTM, College of Built Environment (2023)
The course focuses on the relationship between the ‘ordinary people’ and their everyday landscape to develop knowledge on culture and identity in society. It is designed in three parts. The first part is a field study of landscape as a product of human activities in time and space. The second is a studio workshop to organize and compile information, which are procured during the field study, into maps, photographic journals, and written report. The third is an analytical exercise to examine the significant of cultural meanings and values attached to the landscape.